Digitalisasi pembayaran dan strategi branding UMKM: Studi kasus pada Apotik Kasih Ibu dan usaha Toko Kue Herawati di Kecamatan Balige dalam perspektif SDGs - Haikal Dzikri Daulay; Nur Sa’diah Saragih; Rodiatul Husna; Shopi Regina; Zuhrinal M. Nawawi (BADAN PENERBIT STIEPARI PRESS, 2026)
This community engagement program demonstrated how the digitalization of payment systems and branding strategies can enhance the competitiveness of micro, small, and medium enterprises (MSMEs) in Indonesia’s growing digital economy. The program analyzed the implementation of the Quick Response Code Indonesian Standard (QRIS) at Kasih Ibu Pharmacy and the branding development process through the creation of the MSME business name Herawati Cake. Using a descriptive qualitative approach, the study collected data through direct observation, semi-structured interviews, and documentation involving business owners and customers.The implementation of QRIS significantly improved transaction efficiency, transparency, and convenience, while promoting financial inclusion and aligning with SDG 9 (Industry, Innovation, and Infrastructure). Concurrently, the branding initiative through the name Herawati Cake strengthened the enterprise’s business identity, enhanced consumer trust, and contributed to SDG 8 (Decent Work and Economic Growth) by supporting sustainable local entrepreneurship.Overall, this community engagement activity provided empirical evidence that digital payment adoption and strategic branding serve as practical instruments for MSMEs to adapt to technological change, increase customer engagement, and actively contribute to Indonesia’s sustainable development goals.